2010
DOI: 10.1161/circgenetics.110.936955
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nonmajor Histocompatibility Complex–Linked Loci From Mouse Chromosome 17 Confer Susceptibility to Viral-Mediated Chronic Autoimmune Myocarditis

Abstract: Background-Development of viral-induced chronic myocarditis is thought to involve both environmental and genetic factors. However, to date, no susceptibility genes have been identified. Methods and Results-We sought to identify loci that confer susceptibility to viral-induced chronic myocarditis with the use of chromosome substitution strain mice that are composed of 1 chromosome from the disease susceptible A/J strain on an otherwise resistant C57BL/6 background. By this method, we identified chromosome 17 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
(35 reference statements)
3
6
0
Order By: Relevance
“…The MHC genes have been linked to susceptibility to myocarditis in both humans and experimental mouse models (13,14).…”
mentioning
confidence: 99%
“…The MHC genes have been linked to susceptibility to myocarditis in both humans and experimental mouse models (13,14).…”
mentioning
confidence: 99%
“…Poffenberger et al demonstrated that in the absence of IL-6, a greater early immune response occurred, instigating a severe chronic disease pathology (Poffenberger et al 2009). Recently, Poffenberger et al described susceptibility loci on chromosome 17 that implicate the highly suggested genetic component as a factor dictating viral myocarditis pathogenesis (Poffenberger et al 2010). Though work from our lab has contributed a great deal to the understanding of coxsackievirus B3-induced myocarditis, there remains many unanswered questions with regards to the true key immune players that dictate disease pathogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that the induction of disease by immunization with cardiac myosin can only be successful in genetically susceptible mice . We suggest that the complex genetics of the host therefore determines whether an infection will resolve or proceed to an adverse autoimmune outcome (Poffenberger et al 2010). Identifying particular traits that favour susceptibility or resistance to an autoimmune incidence helps us understand how infectious diseases culminate in autoimmune disease.…”
Section: Experimental Autoimmune Myocarditismentioning
confidence: 99%
“…In mice, several genes have been identified conferring susceptibility for viral induced-chronic myocarditis. Some of them belong to major histocompatibility complex, others are close to loci for autoimmune diseases, highlighting the link between genetics and immune response to viral injury and DCM [4]. The link between genetic susceptibility, related immune response, and DC is not proven in human.…”
Section: Discussionmentioning
confidence: 99%